Nerve Conduction Studies in Patients With Ankylosing Spondylitis - (:unkn) unknown (NATL MED ASSOC, 2010)
Objectives: The objective of this study was to investigate any relationship between peripheral neuropathy and ankylosing spondylitis (AS), and to evaluate the peripheral nervous system of AS patients and disclose any relationship. between neuropathy and disease-related parameters. Patients and Methods: Thirty-two AS patients without any symptoms of neuropathy were prospectively recruited in 2 centers. They were substantially evaluated both for AS and evidence of peripheral neuropathy. Motor and sensory nerve conduction studies with regard to median, ulnar, common peroneal, tibial, and sural nerves were performed. Nerve conduction study results of AS patients were compared with those of 30 healthy subjects. Results: Six patients (18.8%) were diagnosed to have involvement of the peripheral nervous system (5 sensory and 1 sensorimotor), and 7 patients (21.9%) had focal nerve involvements (6 had prolonged median distal sensory latency and 1 patient had slowing of the right ulnar nerve motor conduction velocity at the cubital tunnel). Tibial nerve motor conduction velocity was positively correlated with Schober (r = 0.48, p = .03) and chest expansion tests (r = 0.44, p = .05). Sural nerve sensory action potential amplitude was found to be negatively correlated with age (r = -0.53, p = .02) and disease duration (r = -0.55, p = .02). Ulnar nerve motor conduction velocity at the forearm was positively correlated only with Schober values (r = 0.48, p = .03). Conclusions: We imply that the peripheral nervous system can as well be involved as the central nervous system in asymptomatic AS patients. Further studies with larger samples and with longer disease duration are awaited to confirm our results and to unravel its clinical relevance. Other types of neuropathies or the burden of several drugs on peripheral neuropathy also remains to be deciphered.
Keywords: inflammation; neuropathy; PERIPHERAL NEUROPATHY; SYSTEM INVOLVEMENT; AXONAL NEUROPATHY